2017
DOI: 10.1097/md.0000000000006666
|View full text |Cite
|
Sign up to set email alerts
|

Circulating TNF receptors predict cardiovascular disease in patients with chronic kidney disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Higher levels of TNFR1 and TNFR2 have previously been associated with an increased risk of cardiovascular events and mortality in specific patient groups, such as in people with diabetes mellitus, chronic kidney disease, rheumatoid arthritis, or heart failure after myocardial infarction, as well as in the general population . No association with mortality risk was found in patients undergoing hemodialysis .…”
Section: Discussionmentioning
confidence: 98%
“…Higher levels of TNFR1 and TNFR2 have previously been associated with an increased risk of cardiovascular events and mortality in specific patient groups, such as in people with diabetes mellitus, chronic kidney disease, rheumatoid arthritis, or heart failure after myocardial infarction, as well as in the general population . No association with mortality risk was found in patients undergoing hemodialysis .…”
Section: Discussionmentioning
confidence: 98%
“…Tumor necrosis factor-α has been reported to be increased in intracellular aging studies in elderly people, in centenarians and octogenarians with atherosclerosis, and associated with mortality ( 197 202 ). In post-MI patients, a rise in TNF-α increased risk of recurrent cardiac events and in renal patients TNF-α receptors predicted cardiovascular disease ( 203 205 ). In genetic studies, the A allele of TNF-α 308 G/A gene associated with risk for MI, whereas TNF-α polymorphisms and TNF-α itself, have been variably associated with increased Alzheimer’s disease risk ( 206 210 ).…”
Section: Pro-inflammatory and Anti-inflammatory Cytokine Dysregulatiomentioning
confidence: 99%
“…Chitotriosidase-1 implicated in the development of atherosclerosis (Boot et al, 1999;Kitamoto et al, 2013) P-selectin, IL-8 reported to be significantly higher in unstable coronary heart disease patients in comparison to stable coronary heart disease patients or controls (Romuk et al, 2002) JAM-A, P-selectin, and MMP-1 reported in different studies to induce platelet activation and to enhance aggregation and thrombus formation (Babinska et al, 2002;Galt et al, 2002;Thé orêt et al, 2011) CDCP1 genetic copy number variants in the CDCP1 gene locus were found to be significantly associated with myocardial infarction (Shia et al, 2011) CD40 ligand reported to be mainly derived from activated platelets and to contribute to the pathophysiology of atherosclerosis (Lievens et al, 2010;Pamukcu et al, 2011) Caspase-3 expressed in atherosclerotic plaques and its levels are correlated with measures of atherosclerosis (Matulevicius et al, 2008) TNF receptors reported to be negatively correlated with kidney function and to predict cardiovascular disease in patients with chronic kidney disease (Bae et al, 2017) TNF, tumor necrosis factor.…”
Section: Proteins Previous Findingsmentioning
confidence: 99%